PENINGKATAN EXPECTED RETURN MELALUI PENGELOLAAN SYSTEMATIC RISK DAN UNSYSTEMATIC RISK - Mukarromah, Sitti; Suryo, Ibnu; Meliana, Peni Febrianita (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to demonstrate the extent of the influence of systematic risk and unsystematic risk on the expected return of food and beverage companies listed on the Indonesia Stock Exchange (BEI) in 2021. The research employs a descriptive quantitative method, collecting data through recording and literature review. Historical data analysis on investor behavior, such as systematic risk, is observed by measuring beta (Î²), while unsystematic risk is observed from the residual variance (Ïƒ2ei2) of each stock. Return is calculated from the difference in stock prices divided by the stock price over a specific period. To examine how systematic risk and unsystematic risk affect the expected return for investors, this study uses multiple linear regression analysis with the Statistical Package for Social Science (SPSS). Partial test results indicate that systematic risk does not positively affect the expected return, whereas unsystematic risk does. However, the combined test results show that both risks positively impact the expected return. When deciding to invest in a particular company, investors consider both return and risk. Therefore, risk management is closely related to a company's sustainability.